Adequação da demanda de crianças e adolescentes atendidos na Unidade de Emergência em Maceió, Alagoas, Brasil Meeting the demand for services of children and adolescents at the Emergency Unit in Maceió, in the Brazilian State of Alagoas - Dione Alencar Simons; Isabella Lopes Monlleó; Sofia Alencar Simons; José Luiz Araújo Júnior (Instituto Materno Infantil de Pernambuco, 2010)
OBJETIVOS: avaliar a adequação da demanda de crianças e adolescentes atendidos na Unidade de Emergência Doutor Armando Lages em Maceió - Alagoas, Brasil. MÉTODOS: estudo observacional-transversal de 2153 registros de crianças e adolescentes atendidos na Unidade de Emergência, em 1998, 2001 e 2004. Variáveis: sexo, idade, setor e horário do atendimento, procedência, internação, tipo de agravo e adequação da demanda, segundo critério de Furtado et al. Para testar associações entre variáveis de interesse foi utilizado teste do Qui-quadrado, adotandose nível de confiança de 95%. RESULTADOS: entre os 2153 registros analisados, 1792 (83,2%) foram classificados como não adequados. Predominaram usuários do sexo masculino (1252 - 58,2%), entre 10 e 18 anos (931 - 43,2%), residentes em Maceió (1742 - 81,1%), atendidos à tarde (800 - 37,2%), no setor de pediatria e com agravos do Capítulo XIX da Classificação Internacional de Doenças (1039 - 48,3%). A não adequação da demanda foi maior no sexo feminino, entre 10 e 18 anos, atendida no horário da manhã e residente próximo à Unidade de Emergência. CONCLUSÕES: verificou-se alto percentual de não adequação da demanda de crianças e adolescentes à Unidade de Emergência. Esse resultado sinaliza para o não atendimento às necessidades de saúde na rede básica do Sistema Único de Saúde em Alagoas. OBJECTIVE: to evaluate the extent to which the demand for services from children and adolescents are met by the Doutor Armando Lages Emergency Unit in Maceió, in the Brazilian State of Alagoas. METHODS: an observational cross-section study was carried out of 2,153 medical records of children and adolescents attending the Emergency unit in 1998, 2001 and 2004. The variables were sex, age, sector and time attended, place of residence, hospitalization, type of injury and extent to which the demand was met, according to the criterion established by Furtado et al. The chi-squared test was used to investigate associations between the variables under study, with a confidence level of 95%. RESULTS: of the 2,153 medical records analyzed, 1792 (83.2%) were classified as inadequate. Most patients were male (1252 - 58.2%), aged between 10 and 18 years (931 - 43.2%), resident in Maceió (1742 - 81.1%), attended in the afternoon (800 - 37.2%), at the Pediatrics Centre with injuries covered by Chapter XIX of the International Classification of Diseases (1039 - 48.3%). There were more inadequate medical records for females aged between 10 and 18 years, attended in the morning, residing in close proximity to the Emergency Unit. CONCLUSIONS: there was a high percentage of inadequate service provision for children and adolescents at the Emergency Unit. This result suggests the health needs of this group are not being met by the basic National Health System in the State of Alagoas.